Bi-layer materials based on thermoplastic corn starch, polylactic acid and modified polypropylene (2020)
Currently, the development of environmentally friendly materials with suitable properties for industrial use has become ofgreat importance. In this work, bilayer materials were developed by assembling thermoplastic- corn starch monolayers (TPS)combined with semi-crystalline polylactic acid (PLAs) monolayers and maleic anhydride grafted polypropylene (PPMA). Thepresence of a potassium sorbate solution was evaluated as interface material. Structural properties (FTIR and SEM), interactionswith water (water vapor transmission rate, solubility in water and moisture content) and biodegradation of the materials wereevaluated. FTIR spectra showed that potassium sorbate promotes chemical interactions between TPS monolayers (-OH group)and PLA monolayers (C=O group) or PPMA(C-O-C, C-O, C-H groups). For their part, SEM micrographs reveal that whenadding potassium sorbate, higher interfacial adhesion develops between TPS and PPMAthan between TPS and PLAs. As for theinteractions with water, when using a PLA or PPMAmonolayer, due to its hydrophobic characteristics, the high permeability towater vapour and the sensitivity to liquid water that starch-based materials present would be avoided. Finally, the biodegradationtest showed that TPS biodegrades faster than other materials, followed by PLA. The results obtained are interesting since theaddition of an adhesive material to assemble the low chemical affinity monolayers would be avoided. The developed materialsexhibit great potential for application as packaging in the food industry.